Chitosan polyvinyl alcohol blend films for ibuprofen encapsulation: Fabrication, characterization and kinetics. (November 2020) - Aycan, Didem; Yayla, Neslihan Alemdar; Aydin, Yasar Andelib
Highlights: Homogeneous films of chitosan, polyvinyl alcohol, genipin and ibuprofen were casted. Tensile strength was improved by 1.8 folds at 0.25 mM genipin concentration. Crosslinking avoided burst release and provided a longer elution span. Ibuprofen was released as a result of diffusional and relaxational transport mechanisms. Abstract: Hereby, the effectiveness of ibuprofen release from chitosan/polyvinyl alcohol blend films prepared by solvent casting method was studied as a function of blend composition and cross-linking density. Genipin was used as the cross-linker. Miscibility of blend components was verified by FTIR and SEM analyses. Based on the results of ninhydrin assay, optimal genipin concentration was determined as 0.25 mM. Genipin induced inter and intramolecular hydrogen bonding aided in the enhancement of tensile strength and mechanical stability as shown with swelling tests. Concordantly, burst release was hindered and more efficient release profile was obtained for crosslinked blend. The kinetics of ibuprofen release was best described by Korsmeyer Peppas model implying that diffusion and polymer relaxation were the underlying mechanisms for either non-crosslinked or genipin cross-linked blends. Over 96% of cell viability was recorded in WST-1 assay. All these results suggested that ibuprofen encapsulated chitosan polyvinyl alcohol blends crosslinked by genipin could be used as pain suppressing wound dressing material. Graphical abstract: Image, graphical abstract